Magnesium-zinc-calcium alloy intravascular absorbable stent material and preparation method thereof

Through the preparation of intravascular absorbable stent materials of magnesium-zinc calcium alloy, the corrosion and insufficient mechanical properties of traditional vascular stents are solved, and the excellent biocompatibility and mechanical properties of magnesium-zinc calcium alloy are achieved, which is suitable for vascular and orthopedic applications.

CN119158088APending Publication Date: 2024-12-20SU ZHOU XIANG QIN YI LIAO KE JI YOU XIAN GONG SI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410129699.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-01-30
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Traditional metal non-absorbent vascular stents have clinical problems such as acute subacute thrombosis, inflammatory response and restenosis formation. The rapid corrosion and mechanical properties of magnesium alloys in the physiological environment limit their application, and rare earth metals may produce human organs. Side effects lead to further improvement in the corrosion resistance and mechanical properties of the magnesium, zinc and calcium alloy system.

Method used

The magnesium-zinc calcium alloy is used to absorb stent material in the blood vessels, with components of 1-6% zinc, 0.1%-0.6% calcium, and the rest are magnesium. It is prepared by remelting method and heat treatment and extrusion process optimization, and observation with scanning electron microscopy Microstructure, controlling the secondary phase distribution of the alloy to improve corrosion resistance and mechanical properties.

Benefits of technology

It has achieved excellent biocompatibility and mechanical properties of magnesium-zinc calcium alloy stents, reduced corrosion rate, improved mechanical strength and corrosion resistance, and is suitable for use in organ applications such as vascular and orthopedics, and has shown good performance in cytotoxicity tests. cell viability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119158088A_ABST
    Figure CN119158088A_ABST
Patent Text Reader

Abstract

The invention discloses a magnesium-zinc-calcium alloy intravascular absorbable stent material and a preparation method thereof. The magnesium-zinc-calcium alloy intravascular absorbable stent material is prepared from the following components in percentage by mass: 1-6% of zinc, 0.1-0.6% of calcium and the balance of magnesium. The preparation method has the beneficial effects that the stent material is prepared from the magnesium-zinc-calcium alloy in a specific proportion, and the stent material has excellent biocompatibility and mechanical properties through optimization of a preparation process and surface treatment, and is convenient for clinical popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of vascular stents and related medical devices, and in particular to a magnesium-zinc-calcium alloy intravascular absorbable stent material and a preparation method thereof. Background Art

[0002] At present, vascular stents are the most commonly used method for treating intravascular plaque stenosis or occlusion; however, traditional metal non-absorbable stents have difficult-to-solve clinical problems such as acute and subacute thrombosis, inflammatory response and restenosis formation; in order to overcome these clinical pain points, magnesium alloy vascular stent materials and stents have received increasing attention; magnesium alloys have good biocompatibility, bioactivity and absorbability, and are widely considered to be an ideal vascular stent material; however, due to the rapid corrosion of magnesium alloys in physiological environments and the lack of sufficient mechanical properties, their application is limited; the addition of alloying elements such as calcium and zinc can improve the mechanical properties and corrosion behavior of magnesium alloys, so the present invention selects magnesium-zinc-calcium alloy as a vascular stent Materials development; As a metallic implant material, Mg is biodegradable, biocompatible, and has a Young's modulus similar to that of bone, thereby alleviating the stress shielding effect; however, the application of pure Mg (P-Mg) in load-bearing implants is limited due to its poor mechanical properties and relatively high corrosion rate, depending on the impurity level; therefore, several alloy systems have been developed to overcome these shortcomings; alloying elements such as Al, Li, Zr and rare earth metals such as Y, Nd, Gd are used because of their beneficial effects on mechanical properties; but although these alloy systems show good biocompatibility in in vitro and in vivo experiments, the possible side effects of rare earth metals and aluminum on human organs remain controversial.

[0003] Over the years, based on the research of the National 863 Project, AZ31 and other intravascular absorbable stents, we have further studied the Mg alloy system composed of Ca and Zn. Ca and Zn were selected as alloying elements because of their biocompatibility and grain refining effect on Mg; Ca is one of the main elements in human bones, while Zn enhances immunity and other biological mechanisms in the body; It is reported that the Mg alloy system containing Ca and Zn has been successfully applied to small fractures of the hand and wrist without adverse effects; A recent study also showed that the Mg-Zn-Ca system exhibited significantly improved formability compared with commercially available Mg-Al alloys; However, the main disadvantage of the alloy system composed of Zn and Ca is the high degradation rate caused by microgalvanic corrosion, and solution treatment can improve the corrosion resistance by reducing the secondary phase; However, it reduces the mechanical strength. There have been studies to improve mechanical and corrosion properties by finely distributing secondary phases through hot working methods such as extrusion and rolling; however, despite the improvement in mechanical properties of Mg-Zn-Ca alloys, the corrosion rate is still greater than that of extremely pure (99.9%) P-Mg; controlling a small range of alloying elements may be the key to improving the corrosion resistance of Mg-Zn-Ca alloys; according to previous studies, unresolved secondary phases also exist during heat treatment after plastic deformation, which delays the uniform distribution of secondary phases. Under equilibrium conditions, the maximum solubility of Ca in Mg is only 0.2wt% at 23℃ and 1.35wt% at 516.5℃; when 4wt% Zn is added, the maximum solubility of Ca in Mg is further reduced to 0.04wt% at 368℃. Therefore, a small amount of Ca can greatly affect the properties of the Mg-Zn-Ca system due to the significant change in the distribution of secondary phases; however, many studies on the Mg-Zn-Ca system have mainly focused on the alloy composition limited to the solid solution, and failed to clearly understand the effect of the Ca solid solution component on the Mg-Zn alloy. Summary of the invention

[0004] The purpose of the present invention is to solve the above problems and to design a magnesium-zinc-calcium alloy intravascular absorbable stent material and a preparation method thereof.

[0005] The technical solution of the present invention to achieve the above object is a magnesium-zinc-calcium alloy intravascular absorbable stent material, which is composed of the following components in mass percentage: 1-6% zinc, 0.1%-0.6% calcium, and the rest magnesium.

[0006] As a further supplement to the technical solution, the absorbable stent material is tested by soaking it in Hank's solution for 7-30 days.

[0007] As a further supplement to the technical solution, it also includes a small amount or trace amount of elements such as manganese, iron and rare earth elements such as zirconium, neodymium and gadolinium.

[0008] A method for preparing a magnesium-zinc-calcium alloy intravascular absorbable stent material comprises the following steps:

[0009] (1) Mg alloy was prepared by remelting in Ar gas atmosphere using high purity Mg, Ca and Zn metals;

[0010] (2) preparing the Mg alloy at 740°C for 100 min;

[0011] (3) The molten metal was then poured into a mold preheated to 200°C, and the cast alloy was heat treated at 420°C for 20 h;

[0012] (4) subsequently quenching in water;

[0013] (5) The alloy was further extruded at 320°C with an extrusion ratio of 38.95 and a punching speed of 0.2 mm / s.

[0014] As a further supplement to the technical solution, the microstructure of the alloy was observed using a scanning electron microscope in the cast state, heat-treated state, extruded state and after being immersed in Hank's solution.

[0015] As a further supplement to the technical solution, after the sample is cut in the preparation stage, it is ground with SiC paper and finely polished with diamond powder.

[0016] As a further supplement to the technical solution, the SiC paper has a particle size of 2000.

[0017] As a further supplement to the technical solution, the particle size of the diamond powder is 0.25-3 μm.

[0018] A magnesium-zinc-calcium alloy intravascular absorbable stent material and a stent made by a preparation method and related medical devices are used in blood vessels, orthopedics and various organs.

[0019] The beneficial effect is that the stent material is made of a magnesium-zinc-calcium alloy in a specific proportion, and through optimized preparation process and surface treatment, it has excellent biocompatibility and mechanical properties, making it easy for enterprises to promote and use it. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Phase diagram of Mg-2% Zn-Ca;

[0021] Figure 2 SEM image of Mg-Zn-Ca alloy after heat treatment;

[0022] Figure 3 SEM images of Mg-Zn-Ca alloy after heat treatment and extrusion;

[0023] Figure 4 TEM image of the secondary phase of Mg-Zn-Ca alloy after extrusion;

[0024] Figure 5 Study on corrosion characteristics of magnesium-zinc-calcium alloy;

[0025] Figure 6 Study on the dependence of Zn content on Ca content and mechanical properties in magnesium alloys;

[0026] Figure 7 The integrity of the magnesium-zinc-calcium alloy and the mechanical properties were further tested after immersion;

[0027] Figure 8 Cytotoxicity test of magnesium-zinc-calcium alloy;

[0028] Fig. 9 Intravascular absorbable stent made of magnesium-zinc-calcium alloy. DETAILED DESCRIPTION

[0029] In order to make the technical solution more clear to those skilled in the art, Figure 1-9 The technical solution of the present invention is described in detail:

[0030] A magnesium-zinc-calcium alloy intravascular absorbable stent material is composed of the following components by mass percentage: 1-6% zinc, 0.1%-0.6% calcium, and the rest magnesium.

[0031] 1. Material Preparation

[0032] We prepared Mg alloy using high purity Mg (99.99%), Ca (99.9%) and Zn (99.9%) metals by remelting method in Ar gas atmosphere. The Mg alloy was prepared at 740℃ for 100min. The molten metal was then poured into a mold preheated at 200℃. The cast alloy was heat treated at 420℃ for 20h. It was then quenched in water. The alloy was further extruded at 320℃ with an extrusion ratio of 38.95 and a punching speed of 0.2mm / s.

[0033] During the preparation of magnesium alloys, the alloys were observed at the following stages of preparation: (i) as-cast, (ii) as-heat-treated, (iii) as-extruded, and (iv) after immersion in Hank's solution. The microstructure of the alloys was observed using scanning electron microscopy (SEM). The samples of each preparation stage were cut, ground with SiC paper (up to 2000 grit), and finely polished with diamond powder (0.25-3 μm). Energy dispersive spectroscopy (EDS) was used to characterize the chemical composition of the alloy phases. The selected area diffraction pattern (SADP) of the precipitates was studied using a transmission electron microscope (TEM, TitanTM80–300).

[0034] The present invention characterizes the difference between a solid solution Mg-2%Zn-0.1%Ca alloy and a Mg-2%Zn-0.3%Ca alloy without a solid solution region. 1). SEM images of cast Mg-2%Zn-xCa (x=0, 0.1, 0.3wt%) show that the secondary phase of the 2%Zn alloy has equiaxed grains (size 3μm). When Ca is added to the 2%Zn alloy, the proportion of the secondary phase distributed along the grain boundaries increases. EDS results and Mg-Zn-Ca phase diagrams show that the Mg-Zn phase is formed in the 2%Zn alloy and the Ca2Mg6Zn3 phase is formed in the Ca-added alloy. The addition of Ca to the Mg-Zn alloy delays the formation of the Mg-Zn phase and promotes the formation of Ca2Mg6Zn3.

[0035] Our study showed that no secondary phases were observed in the Mg-2%Zn and 0.1%Ca alloys after heat treatment of 0.1%Ca and 0.3%Ca alloys. This indicates the dissolution of secondary phases in the Mg matrix. Most of the Ca2Mg6Zn3 dissolved in the cast alloy in the Mg matrix. However, equiaxed secondary phases were still observed in the 0.3%Ca alloy. Similar research results have not been reported. The extruded alloy without Ca had no secondary phases, but the 0.1%Ca alloy had fine (200nm) and well-dispersed Ca2Mg6Zn3 grains. However, coarse (4μm) Mg2Ca, as well as small and well-dispersed Ca2Mg6Zn3 were observed in the 0.3%Ca alloy. Calcium content is an important factor affecting the grain size of extruded alloys. The results of small amount of Ca addition in Mg-Zn alloys show that increasing the Ca content can effectively reduce the grain size.

[0036] The secondary phases in the extruded 0.1% and 0.3%Ca alloys were further analyzed by transmission electron microscopy. The TEM images of the extruded 0.1% and 0.3%Ca alloys showed that the addition of a small amount of Ca to the Mg-Zn alloys could effectively reduce the grain size from 24.83±8.29μm for 2%Zn to 6.45±1.79μm and 1.12±1.39μm for 0.1% and 0.3%Ca alloys.

[0037] 2. Corrosion characteristics

[0038] The corrosion characteristics test was performed and illustrated by collecting hydrogen gas from extruded samples immersed in Hank's solution for 7 days. In general, the degradation process of Mg in electrolyte can be represented by the reaction in the following formula.

[0039] Mg+2H2O Mg(OH)2+H2. Compared with other Zn content samples (0.4wt%-0.6wt%), the 2% Zn alloy has the lowest hydrogen content (0.038ml / cm 2). The hydrogen released by 0.1%Ca alloy, P-Mg and 0.3%Ca alloy are 0.07, 0.123 and 0.148 ml / cm, respectively. 2 The corrosion potential and corrosion current density were calculated from the polarization curves using the Tafel extrapolation method. The results show that the corrosion potential of the alloys decreases with increasing Ca addition. The cathode curve gradients of 0.3% Ca and P-Mg alloys are steeper than those of other samples, but the cathode curve gradients of 2% Zn and 0.1% Ca alloys are relatively low within the applied potential range. The corrosion current densities of 0.3% Ca, P-Mg, 0.1% Ca and 2% Zn alloys are reduced to 17×10 -6 , 14×10 -6 , 4.9×10 -6 and 4.4×10 - 6 A / cm 2 .

[0040] The microstructure of the cross section of the 0.1% and 0.3% Ca alloys after immersion in Hank's solution for 7 days observed that the corrosion layer of the 0.1% Ca alloy was uniform and very thin, <3μm, while the thickness of the corrosion layer of the 0.3% Ca alloy was 3–30μm, and many corrosion signs were detected. The corrosion near the coarse secondary phase along the extrusion direction seemed to be accelerated. It was further found that there seemed to be a relationship between the decrease in Zn content in the Mg matrix and the increase in secondary phase formation. According to the calculation of the PANDAT program (version 7), the secondary phase of the alloy increased with the increase of Ca content. We further studied the open circuit potential (OCP) of the intermetallic compound. The potential of P-Mg increased with the addition of Zn, from -1.68V (0at% Zn) to -1.5V (1.3at% Zn), and the Ca potential also increased from -1.9V (0at% Zn) to -1.85V (1.5at% Zn) with the addition of Zn.

[0041] We found that the corrosion rate of the 0.1%Ca alloy was lower than that of P-Mg and similar to that of the 2%Zn alloy. However, the corrosion rate of the 0.3%Ca alloy was higher than that of P-Mg. The drastic variation in corrosion rate with Ca content within a small range may be due to the behavior of Zn in the matrix. The addition of Zn improves corrosion resistance by increasing the potential of the Mg matrix. However, with the addition of Ca, the solubility of Zn in the Mg matrix decreases, resulting in a gradual decrease in the Mg potential. The results show that corrosion resistance is achieved by controlling the potential gap of the phases, even in alloys with many secondary phases. Therefore, the corrosion behavior of Mg is affected by the potential difference between the secondary phases more than the volume fraction of the secondary phases.

[0042] 3. Mechanical properties

[0043] The yield strength, ultimate strength and elongation at break of the 2% Zn alloy were 153.4 ± 1.2 MPa, 238.3 ± 0.8 MPa and 16.2 ± 0.8%, respectively. The strength and elongation of the 0.1% Ca alloy were both improved to 278.8 ± 5.2 MPa and 26.1 ± 1.6%. However, when the Ca content was increased to 0.3%, the elongation of the alloy decreased from 26.1 to 17.4% despite the significant improvement in strength. Based on the Hall-Petch relationship between grain size and yield strength, the yield strength is proportional to the reduction in grain size with the addition of Ca. In order to evaluate the integrity of the mechanical properties in a corrosive environment, tensile tests were performed on the samples with Ca addition after immersion in Hank's solution for 30 days. After immersion, the yield strength, ultimate strength and elongation of the 0.1%Ca alloy were 239.4±3.6MPa, 276.3±5.1MPa and 14.3±4.0%, respectively. This indicates that the strength of the 0.1%Ca alloy remained unchanged, while the elongation decreased slightly. However, the 0.3%Ca alloy showed a greater decrease in strength, elongation and deflection.

[0044] Studies have shown that adding Ca to Mg-Zn alloys can have a positive effect on mechanical properties. The addition of Ca helps the alloy to produce a second phase during plastic deformation (for example, during hot extrusion), which retards grain growth and causes the alloy to have a weaker texture. This phenomenon occurs in the 0.3wt% Ca alloy used in the present study.

[0045] 4. Integrity: Mechanical properties after immersion

[0046] Strength after electrolyte degradation is an important qualification factor for implant materials. Tensile tests were performed after immersion in Hank's solution for 30 days. Interestingly, the mechanical strength of the 0.1%Ca alloy remained unchanged after immersion, while the mechanical strength of the 0.3%Ca alloy dropped sharply. It has been reported that the mechanical strength of the 4wt%Zn-0.2wt%Ca alloy dropped to 70% after immersion for 30d. 0.3%Ca and 4wt%Zn-0.2wt%Ca exhibited rapid corrosion rates due to several secondary elements in the alloys. As mentioned earlier, Ca exceeds the amount that can be completely dissolved in Mg-Zn alloys, which leads to a potential imbalance between the Mg matrix and Ca, Ca2Mg6Zn3, which reduces the corrosion resistance of the alloy and causes localized corrosion, such as pitting. These results indicate that the decline in mechanical properties after immersion is related to pitting. The 0.3%Ca alloy exhibited various pitting sizes of 20–240μm, while the pitting size of the 0.1%Ca alloy was less than 20μm.

[0047] 5. Cytotoxicity assay

[0048] We performed a cell viability test using a minimal culture medium solution as a negative control. The control group was cultured in the cell culture medium for 24 h. Cell viability that was about 80% lower than the negative control was considered cytotoxic. The results showed that the cell viability of all samples (1d) was more than 100%. This means that the culture medium corroded by the scaffold did not affect the cell viability.

[0049] However, the cell viability decreased with culture time (1, 3, and 7 days), which was due to a series of complex factors, including pH and ion activity. The degradation of Mg is related to pH and ion activity. Therefore, the low cell viability (<80%) of the 0.3%Ca alloy may be related to the high corrosion rate. The cells may have difficulty surviving in the culture medium containing a large amount of Mg and Zn ions and alkaline conditions. However, the cell viability of the 0.1%Ca alloy was above 80% throughout the experimental period. This may be due to its better corrosion resistance.

[0050] In summary, the present study shows that in the Mg-2% Zn alloy system, the addition of Ca promotes the formation of Ca2Mg6Zn3, and the secondary phase along the grain boundary increases with the increase in Ca addition. However, SEM analysis shows that in the 0.3% Ca alloy, in addition to Ca2Mg6Zn3, a large amount of Mg2Ca is formed. Therefore, 0.3% Ca is difficult to dissolve in the Mg matrix. The Mg+ liquid phase is stable in equilibrium at 416°C. Therefore, the secondary phase may be a liquid phase and then transform into a Ca2Mg6Zn3 eutectic phase composed of Mg.

[0051] The microstructure after extrusion suggests that different secondary phases are present depending on the Ca content. After adding 0.1% Ca, fine and well-dispersed secondary phases were observed, but no secondary phases were formed in the 2% Zn alloy. This phenomenon is caused by dynamic precipitation during hot extrusion. In addition, coarse Mg2Ca was observed in the 0.3% Ca alloy. These results indicate that uniform distribution of secondary phases is possible under solid solution conditions. In addition, grain reduction due to the addition of small amounts of Ca was observed by transmission electron microscopy.

[0052] In both immersion and electrochemical corrosion tests, the 2% Zn alloy exhibited the lowest corrosion rate, and the corrosion resistance gradually decreased with increasing Ca addition. In addition, as found in the open circuit potential analysis, the increase in Ca content led to a steady decrease in the Mg potential due to the reduced solubility of Zn in the Mg matrix. This means that Ca bridges the large potential gap between Ca2Mg6Zn3 in the Mg matrix, which may accelerate the anodic reaction of Mg. Therefore, the potential difference between the secondary phases has a greater impact on the corrosion behavior of Mg than the volume fraction of the secondary phase.

[0053] The addition of 0.1% Ca has a surprisingly positive effect on the mechanical properties of the alloy. The small and well-dispersed Ca2Mg6Zn3 phase in the 0.1% Ca alloy effectively retards grain growth. In addition, the yield strength and elongation of the 0.1% Ca alloy are increased by more than 50% compared with the 2% Zn alloy. However, when 0.3% Ca is added, the decrease in mechanical properties, especially the decrease in elongation, may be caused by the secondary phase (along the extrusion direction) as a crack trigger. Therefore, the continuous secondary phase can improve the mechanical strength but has a negative impact on the machinability. These results are consistent with the results of the corrosion tests.

[0054] In addition, micro-CT scanning showed that the deterioration of mechanical properties after immersion was caused by pitting corrosion. Due to the potential imbalance between the Mg matrix and the secondary phase, local stress concentration is prone to occur in the 0.3%Ca alloy, resulting in the deterioration of mechanical properties. In contrast, the corrosion rate of the 0.1%Ca alloy is relatively slow and the corrosion layer is uniform. This may be the reason why the alloy maintains its strength.

[0055] The 0.1%Ca alloy exhibited more stable cell viability than the 0.3%Ca alloy, which was related to corrosion and pH changes. These results indicate that the Ca content included in Mg-Zn alloys is very important to improve the mechanical and biocorrosion properties for a wide range of applications.

[0056] The specific embodiments are as follows:

[0057] Example 1

[0058] SEM Phase Image Study of Cast Mg-2%Zn-xCa (x=0, 0.1, 0.3wt%) Alloys

[0059] Purpose:

[0060] The addition of a small amount of Ca into the Mg-2%Zn alloy system revealed differences in the characterization between the solid solution Mg-2%Zn-0.1%Ca alloy and the Mg-2%Zn-0.3%Ca alloy without solid solution region.

[0061] method:

[0062] During the sample preparation, the alloys were observed at the following stages of preparation: (i) as-cast, (ii) as-heat-treated, (iii) as-extruded, and (iv) after immersion in Hank's solution. The microstructure of the alloys was observed using scanning electron microscopy (SEM, Check F50); the chemical composition of the alloy phases was characterized using energy dispersive spectroscopy (EDS); and the selected area diffraction pattern (SADP) of the precipitates was studied using transmission electron microscopy (TEM, TitanTM80–300).

[0063] result:

[0064] As shown in the phase diagram ( Figure 1 ), characterizing the difference between the solid solution Mg-2%Zn-0.1%Ca alloy and the Mg-2%Zn-0.3%Ca alloy without solid solution region. Figure 2 The difference in SEM phase images of cast Mg-2%Zn-xCa (x=0, 0.1, 0.3wt%) is shown. The secondary phase of the 2%Zn alloy has equiaxed grains (size of 3μm). When Ca is added to the 2%Zn alloy, the proportion of the secondary phase distributed along the grain boundaries increases. The EDS results and the Mg-Zn-Ca phase diagram show that the Mg-Zn phase is formed in the 2%Zn alloy, and the Ca2Mg6Zn3 phase is formed in the Ca-added alloy. This shows that the addition of Ca in the Mg-Zn alloy delays the formation of the Mg-Zn phase and promotes the formation of Ca2Mg6Zn3 after Ca addition.

[0065] Example 2

[0066] SEM image observation of Mg-Zn-Ca alloy after heat treatment and extrusion

[0067] result:

[0068] like Figure 3 As shown, ac show the SEM images of 2% Zn alloy, 0.1% Ca and 0.3% Ca alloy after heat treatment, respectively. After heat treatment, no secondary phase was observed in the 2% Zn and 0.1% Ca alloys. This can be attributed to the dissolution of the secondary phase in the Mg matrix. Most of the Ca2Mg6Zn3 was dissolved in the cast alloy in the magnesium matrix. However, equiaxed secondary phases were still observed in the 0.3% Ca alloy. According to EDS analysis, the white area (circled in red in the figure) is Ca2Mg6Zn3, and the gray area (circled in yellow in the figure) is Mg2Ca, which includes a small amount of Zn (2.7at%). Other similar studies on the formation of Mg2Ca have not been reported yet. Figure 3 d–f show the microstructures of the 2% Zn, 0.1% Ca, and 0.3% Ca alloys after extrusion, respectively. The extruded alloy without Ca has no secondary phase, but the 0.1% Ca alloy ( Figure 3 e) with fine (~200 nm) and well-dispersed Ca2Mg6Zn3. However, coarse (~4 μm) Mg2Ca, as well as small and well-dispersed Ca2Mg6Zn3 were observed in the 0.3% Ca alloy ( Figure 3 f). Calcium content is also an important factor affecting the grain size of extruded alloys. For the addition of a small amount of Ca in Mg-Zn alloys, increasing the Ca content can effectively reduce the grain size.

[0069] Example 3

[0070] Further analysis of secondary phases in Mg-Zn-Ca alloy after extrusion by transmission electron microscopy

[0071] result:

[0072] like Figure 4 , the secondary phases in the extruded 0.1% and 0.3%Ca alloys were further analyzed by transmission electron microscopy. TEM bright field images of the extruded 0.1% and 0.3%Ca alloys. The image of the 0.1%Ca alloy was taken with the beam incident along the zone axis of the [21-1-0]Mg matrix. SADP of the secondary phases confirmed that it is indeed a result of Ca2Mg6Zn3. The image of the 0.3%Ca alloy was taken with the beam incident along the zone axis of the [15-43]Mg matrix. SADP of the secondary phases confirmed that these phases are a result of Mg2Ca. Figure 4 A, B, C further confirmed that the addition of a small amount of Ca into Mg-Zn alloys can effectively reduce the grain size from 24.83 ± 8.29 μm for 2% Zn to 6.45 ± 1.79 μm and 1.12 ± 1.39 μm for 0.1% and 0.3% Ca alloys.

[0073] Example 4

[0074] Further Study on Corrosion Characteristics of Mg-Zn-Ca Alloy

[0075] method:

[0076] Hank's Balanced Salt Solution Immersion Test

[0077] The immersion tests were conducted in Hank's balanced salt solution. The pH and temperature of Hank's solution were adjusted to 7.4°C and 37°C, respectively. Coin samples with a diameter of 8 mm and a thickness of 1 mm were prepared from the extruded alloy. They were ground with silicon carbide paper (up to 2000 grit), ultrasonically cleaned in ethanol for 10 min, dried in air, and then immersed in Hank's solution.

[0078] Electrochemical measurements:

[0079] Electrochemical measurements were performed in a three-electrode cell using a potentiostat (EG&G PAR Model 263A potentiostat / galvanostat). Magnesium alloy was used as the working electrode. Platinum and Ag / AgCl were used as the counter and reference electrodes, respectively. A potential range was applied to the working electrode at a scan rate of 0.83 mV / s. The corrosion current density (iCole) was estimated using linear regression and Tafel extrapolation to the cathodic and anodic cross sections of the polarization curves. The pH of the corrosive environment was 7.4. Hank's solution was placed in air at 36.5 °C. The sample area exposed to the electrolyte was 0.28 cm 2 .

[0080] result:

[0081] like Figure 5 A, B show the microstructure of the cross-section corrosion of 0.1% and 0.3% Ca alloys after immersion in Hank's solution for 7 days. It was observed that the corrosion layer of the 0.1% Ca alloy was uniform and very thin (~3μm), while the corrosion layer of the 0.3% Ca alloy was thick (3–30μm) and many corrosion signs were detected. The corrosion near the coarse secondary phase along the extrusion direction also seemed to be accelerated. Figure 5 C, D show the EDS results of the corroded surface of the 0.3%Ca alloy. Interestingly, localized corrosion of Ca2Mg6Zn3 was not observed in the calcium-rich area (Mg2Ca).

[0082] This example found that the corrosion rate of the 0.1% Ca alloy was lower than that of the P-Mg and similar to that of the 2% Zn alloy. However, the corrosion rate of the 0.3% Ca alloy was higher than that of the P-Mg. The 0.1% Ca alloy exhibited excellent corrosion resistance.

[0083] Example 5

[0084] Study on the dependence of Zn content on Ca content and mechanical properties in magnesium alloys

[0085] method:

[0086] Mechanical properties measurement

[0087] Tensile tests were performed using a universal testing machine (MTS USA). The tensile test specimens were prepared according to ASTM B557-10. The crossbar speed and gauge length at room temperature were 2 mm / min and 15 mm, respectively. In order to evaluate the changes in mechanical properties after immersion, the samples were immersed in Hank's solution for 30 days. In this test, Hank's solution was changed every 4 days. After immersion, the corrosion products were removed using chromic acid (180 g / L CrO3 + 1 g / L AgNO3 in distilled water) for 1 min.

[0088] result

[0089] like Figure 6 A, shows the dependence of the fraction of secondary phases and Zn content in the Mg matrix on the Ca content. There seems to be a relationship between the decrease of Zn content in the Mg matrix and the increase of secondary phase formation. According to the calculations of the PANDAT program (version 7), the secondary phases of the alloy increase with increasing Ca content. This increase is significantly higher than that of the 0.1-0.3% Ca alloy when the Zn content in the Mg matrix decreases significantly.

[0090] like Figure 6B, shows the nominal stress-strain curve of the room temperature tensile test. The yield strength, ultimate strength and elongation at break of the 2% Zn alloy are 153.4±1.2MPa, 238.3±0.8MPa and 16.2±0.8%, respectively. The strength and elongation of the 0.1% Ca alloy are both improved to 278.8±5.2MPa and 26.1±1.6%. However, when the Ca content is increased to 0.3%, although the strength is significantly improved, the elongation of the alloy decreases from 26.1 to 17.4%. As Figure 6 As shown in C and D, in order to evaluate the integrity of mechanical properties in a corrosive environment, the Ca-added samples were tensile tested after immersion in Hank's solution for 30 days. As shown in the figure, the nominal stress-strain curve after immersion in Hank's solution for 30 days, the yield, ultimate strength and elongation of the 0.1%Ca alloy are 239.4±3.6MPa, 276.3±5.1MPa and 14.3±4.0%, respectively. After immersion, the strength of the 0.1%Ca alloy remained unchanged, while the elongation decreased slightly. However, the 0.3%Ca alloy showed a large reduction in strength, elongation and deviation. It shows that the strength and corrosion resistance of the 0.1%Ca alloy are better than those of the 0.3%Ca alloy.

[0091] Example 6

[0092] Integrity of Mg-Zn-Ca alloy: Further testing of mechanical properties after immersion

[0093] method:

[0094] Micro-CT Scanning

[0095] Siemens Inveon MicroCT was used to scan at 80 kV and 500 μA, and the data were processed using Inveon software. The percentage of stent degradation loss volume (ΔV) and the degradation rate (corrosion rate, CR) after postoperative stent immersion were calculated according to the following formula: ΔV = (V0–Vx) / V0×100%, where V0 is the initial volume of the stent and Vx is the remaining volume of the stent at different time points; CR = (V0–Vx) / (A×t), where A is the initial area of ​​the stent and t is the postoperative time (in years).

[0096] result:

[0097] Strength after electrolyte degradation after immersion is an important qualification factor for implant materials. Tensile tests were performed after immersion in Hank's solution for 30 days. Interestingly, the mechanical strength of the 0.1%Ca alloy remained unchanged after immersion, while the mechanical strength of the 0.3%Ca alloy dropped sharply. The possible mechanism is that Ca exceeds the amount that can be completely dissolved in the Mg-Zn alloy, resulting in a potential imbalance between the Mg matrix and Ca2Mg6Zn3, which reduces the corrosion resistance of the alloy and causes localized corrosion, such as pitting. Figure 7 Micro-CT scans of immersed tensile samples (0.1%Ca and 0.3%Ca) are shown. These results indicate that the degradation of mechanical properties after immersion is associated with pitting corrosion. The 0.3%Ca alloy exhibits a variety of pit sizes ranging from 20–240μm, while the 0.1%Ca alloy has pit sizes less than 20μm.

[0098] Example 7

[0099] Cytotoxicity test of magnesium-zinc-calcium alloy

[0100] method:

[0101] Cytotoxicity assay

[0102] Cytotoxicity assessment for biometric determination is an example of progress in line with ISO10993 standards. The experimental method is as follows. After eluting the specimen in the cell culture medium DMEM (Dulbecco's Modified Eagles Medium) for 1, 3 and 7 days, the vascular cells (L-929) were cultured in each solution for 1 day and the number of surviving cells was determined. The CCK-8 kit with 1XDMEM without serum was used to measure the formazan absorbance and determine the number of surviving cells. The ratio of the marker to the solution was 1cm2 / ml. The test was carried out in an incubator maintained at 37.5% CO2.

[0103] result:

[0104] The cell viability test results of the research samples are as follows Figure 8 As shown, a basic medium solution was used as a negative control. The control group was cultured in cell culture medium for 24 hours. Cell viability that was about 80% lower than the negative control was considered cytotoxic. The results showed that the cell viability of all samples (1d) was more than 100%. This means that the extraction medium did not affect cell viability.

[0105] But the cell viability decreased over time (1, 3, and 7 days), which was due to a series of complex factors, including pH and ion activity. The degradation of Mg is related to pH and ion activity. Therefore, the low cell viability (<80%) of the 0.3%Ca alloy may be related to the high corrosion rate. The cells may have difficulty surviving in the culture medium containing a large amount of Mg and Zn ions and alkaline conditions. However, the cell viability of the 0.1%Ca alloy was above 80% throughout the experimental period. This may be due to its better corrosion resistance.

[0106] Example 8

[0107] Absorbable intravascular stent made of magnesium-zinc-calcium alloy

[0108] The processing method is as follows: the magnesium-zinc-calcium alloy is further processed into an intravascular bioabsorbable stent with a required diameter and length through warm extrusion and cold extrusion, warm drawing and cold drawing, and then through laser hollowing and engraving, and further surface treatment.

[0109] Result: Fig. 9 As shown in the figure, the magnesium-zinc-calcium alloy bioabsorbable intravascular stent prepared by us. Its physical properties, mechanical properties, corrosion properties and cytotoxicity, etc., as described above, are a new type of intravascular absorbable stent with excellent performance, beautiful appearance and practicality.

[0110] The above technical solutions only reflect the preferred technical solutions of the technical solutions of the present invention. Some changes that may be made to certain parts thereof by technicians in this technical field all reflect the principles of the present invention and fall within the protection scope of the present invention.

Claims

1. A magnesium-zinc-calcium alloy intravascular absorbable stent material, characterized in that: The invention is composed of the following components according to mass percentage: 1-6% zinc, 0.1%-0.6% calcium, and the rest magnesium.

2. The magnesium-zinc-calcium alloy intravascular absorbable stent material according to claim 1, characterized in that: The absorbable stent is tested by soaking it in Hank's solution for 7-30 days.

3. The magnesium-zinc-calcium alloy intravascular absorbable stent material according to claim 2, characterized in that: It also contains small or trace amounts of elements such as manganese, iron and rare earth elements such as zirconium, neodymium and gadolinium.

4. The method for preparing a magnesium-zinc-calcium alloy intravascular absorbable stent material according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) Mg alloy was prepared by remelting in Ar gas atmosphere using high purity Mg, Ca and Zn metals; (2) preparing the Mg alloy at 740°C for 100 min; (3) The molten metal was then poured into a mold preheated to 200°C, and the cast alloy was heat treated at 420°C for 20 h; (4) subsequently quenching in water; (5) The alloy was further extruded at 320°C with an extrusion ratio of 38.95 and a punching speed of 0.2 mm / s.

5. The method for preparing a magnesium-zinc-calcium alloy intravascular absorbable stent material according to claim 1, characterized in that: The microstructure of the alloys was observed using scanning electron microscopy in the as-cast, heat-treated, extruded state, and after immersion in Hank’s solution.

6. The magnesium-zinc-calcium alloy intravascular absorbable stent material and the preparation method thereof according to claim 1, characterized in that: After the samples in the preparation stage were cut, they were ground with SiC paper and finely polished with diamond powder.

7. The magnesium-zinc-calcium alloy intravascular absorbable stent material and the preparation method thereof according to claim 1, characterized in that: The SiC paper was 2000 grit.

8. The magnesium-zinc-calcium alloy intravascular absorbable stent material and the preparation method thereof according to claim 7, characterized in that: The particle size of the diamond powder is 0.25-3 μm.

9. A magnesium-zinc-calcium alloy intravascular absorbable stent material and a preparation method thereof according to any one of claims 1 to 8, and the obtained intravascular absorbable stent and various medical devices, characterized in that It can be applied to blood vessels, orthopedics and various organs.